Teaching Grade 4 English in multilingual classrooms: Hedegaards Double Move Revisited - Kotze, Michelle (School of Education, 2023)
For many Grade 4 learners within South Africa, the transition to English as their Language of Learning and Teaching (LoLT) is often turbulent and troublesome due to current approaches and practices falling short or failing to meet the unique contextual needs of their learners. This paper investigates the potential practical applications of Vygotsky's theory of learning and Hedegaard's Double Move in these classrooms, in an attempt to understand if these concepts and methods are or could be utilized to better accommodate for multilingual learners The data for this multiple case study was collected through observations of Grade 4 English Home Language lessons at two rural primary schools within Limpopo, as well as through semi-structured interviews with the participating teachers. Within these English Language classrooms, the utilization by teachers of Everyday Concepts in an attempt to aid in the understanding of Scientific Concepts occur naturally. This occurrence was also often coupled with increased learner engagement. This signifies teachers gravitate towards Hedegaard's Double-Move Method intuitively, despite not having prior knowledge or familiarity with the model, due to its found usefulness by the teacher during instruction. However, due to their lack of knowledge on the model there were no complete Double-Moves throughout the lessons. These findings indicate that a space exists within English Language classrooms for a conscious application of the model. Furthermore, the use by teachers and learners of their mother tongue within the classroom when engaging in discussion or instruction suggests that a place already exists for it and thus could potentially be utilized as a tool to further facilitate learning. With both educators indicating the inability of learners to cope with the transition and, in turn, their struggle to meet the needs of their learners, a need for a new approach clearly exists. This, coupled the positive results within STEM classrooms, both in relation to learners' ability to grasp the content as well as in providing them with the tools to reclaim foreign topics as their own (Hedegaard & Chaiklin, 2005; Hardman & Teschmacher, 2019; Fleer, 2020; Fleer, 2008; Fleer & Ridgway, 2007), led to the assertion that it held the same potential for English Language classrooms.